Dampak dan Tata Kelola Penggunaan AI pada Keputusan Pemasaran dan Etika - Widodo Wibisono; Sri Heneng Prasastono (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2026)
The development of Artificial Intelligence (AI) technology has significantly changed strategy and decision making in marketing management. However, the massive use of AI raises new challenges regarding ethics, transparency and governance. This research aims to analyze the impact of using AI, especially recommender systems and large language models (LLMs), on the effectiveness of marketing decisions, as well as the role of AI governance in controlling emerging ethical issues. The research method uses a quantitative approach with Structural Equation Modeling (SEM) analysis of data collected from 250 marketing professionals in Indonesia. The research results show that the use of AI has a significant positive effect on the effectiveness of marketing decisions (β=0.62, p<0.001), but also raises ethical issues (β=0.48, p<0.01). Ethical issues were proven to reduce the effectiveness of marketing decisions (β=-0.31, p<0.05), while good AI governance was able to moderate the negative impact of ethical issues (β=0.27, p<0.05). These findings underscore the importance of AI governance in building effective and ethical marketing systems.